2009
DOI: 10.1074/jbc.m807012200
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylurea Receptor 1 Mutations That Cause Opposite Insulin Secretion Defects with Chemical Chaperone Exposure

Abstract: The ␤-cell ATP-sensitive potassium (K ATP ) channel composed of sulfonylurea receptor SUR1 and potassium channel Kir6.2 serves a key role in insulin secretion regulation by linking glucose metabolism to cell excitability. Mutations in SUR1 or Kir6.2 that decrease channel function are typically associated with congenital hyperinsulinism, whereas those that increase channel function are associated with neonatal diabetes. Here we report that two hyperinsulinism-associated SUR1 missense mutations, R74W and E128K, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 38 publications
0
54
0
Order By: Relevance
“…The central role of the K ATP channel in beta cell function is highlighted by deficiencies in both first and second phase GSIS in islets from sulfonylurea 1 (SUR1) −/− and ATP-sensitive inward rectifier potassium channel (KIR6.2) −/− mice [10]. In humans, inappropriate inhibition or activation of K ATP channel activity arising from mutations in KIR6.2 and SUR1 underlie congenital hyperinsulinaemia or neonatal diabetes, respectively [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The central role of the K ATP channel in beta cell function is highlighted by deficiencies in both first and second phase GSIS in islets from sulfonylurea 1 (SUR1) −/− and ATP-sensitive inward rectifier potassium channel (KIR6.2) −/− mice [10]. In humans, inappropriate inhibition or activation of K ATP channel activity arising from mutations in KIR6.2 and SUR1 underlie congenital hyperinsulinaemia or neonatal diabetes, respectively [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The hyperinsulinism E128K mutation disrupts channel trafficking and reduces channel function through poor surface expression (16). After rescue to the cell surface by a chemical chaperone, the E128K mutant channels are hyperactive with a lower than normal ATP sensitivity like the F132L mutants, although they exhibit an abnormally low P o (25). The F132L and E128K mutations cause therefore an abnormally high activity through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation from single-channel records (supplemental Fig. S4) yielded P o ϭ 0.073 Ϯ 0.02 (n ϭ 7) for SUR2A E126A , significantly lower than for wild type and equivalent to Kir6.2⌬C36 (6,7,23,25).…”
Section: Mgadp Binding To Sur Protects Kir62 From Rhodaminementioning
confidence: 99%
“…E128K mutation prevents efficient surface expression of the channel; we have previously shown that this defect is partially corrected by treating cells with a K ATP channel antagonist, tolbutamide, which acts as a chemical chaperone. 15 Cells expressing the E128K mutation were therefore pre-treated with 300 μM tolbutamide overnight to facilitate surface expression. Tolbutamide was then washed out for 2 hours prior to recording to remove its inhibitory effect on channel activity.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%